Long-term results of a primary angioplasty program in patients over 80 years of age - Lorenzo Hernando Marrupe (Permanyer, 2021)
ABSTRACT Introduction and objectives: There is scarce information available on the long-term outcomes of primary angioplasty (PA) in patients over 80 years of age. Our objective was to analyze the characteristics and results of PA in these patients and recognize the prognostic factors and long-term survival. Methods: Observational and retrospective single-center study of consecutive patients over 80 years of age treated with PA between January 2013 and September 2019. A long-term clinical follow-up was performed (mean follow-up of 29 ± 25 months). Results: The study included 133 patients (mean age 85.3 ± 3.8 years and 57 women [43%]). Seventeen percent of the patients were in Killip class III-IV at admission. The mean Charlson Comorbidity index was 2.3 ± 1.6. During the hospitalization, almost half of the patients developed heart failure and mortality rate was 18%. The overall mortality rate at the follow-up was 23%, yet 97.2% of the deaths were due to non-cardiac causes. The independent predictors of overall mortality at the follow-up were chronic kidney disease (HR, 5.7; 95%CI, 1.29-25.5; P = .022), and a Charlson Comorbidity index > 2 (HR, 2.57; 95%CI, 1.07-6.18; P = .035). Conclusions: Patients over 80 years of age treated with PA have high in-hospital and long-term mortality...